Influence of Trace Elements in Cemented Carbide Production - ALIZADEH, E. (Asian Journal of Chemistry, 2010)
Trace elements ranging between 10 and 200 ppm, added to tungsten blue oxide prior to reduction, appear to have a considerable influence on the reduction kinetics and properties of tungsten powders. Marked effects on the grain growth, shape and size of the tungsten crystallites, the Scott density, the grain size distribution and the degree and solidity of agglomerations can be observed even though the impurity elements are partially volatilized during reduction. In order to determine the effects of interactions between impurities, powders containing more than one trace element at a time were tested. The amount of impurity elements present in tungsten powders after reduction can be further reduced by a carburization reaction. The final concentration of impurities remaining in the tungsten carbide after carburization of the tungsten powder depends on the nature of the element and of the chemical compound added as well as on the time and temperature of the heating cycle. Distinct influences of the trace impurities on the grain growth and on the properties of tungsten carbide powder were observed. In tungsten carbide powders, grain size and grain size distribution, as well as the size of the single crystalline domains within the polycrystalline tungsten carbide grains, are influenced by impurities. The oxygen content and mining behaviour of the powder also depend on foreign elements, even though their concentration is very low in most cases after carburization. Impurities also appear to have a remarkable influence on the grain growth of tungsten carbide crystals during liquid phase sintering in molten cobalt and consequently on the final structure of cemented carbides.